Discussion on "An effective method for the explicit solution of sequential problems on the real line" by Sören Christensen. Issue 1 (2nd January 2017) - Irle, Albrecht
ABSTRACT: Based on the thoughtful and inspiring work presented by Professor Christensen, the possibility of the treatment of stopping problems with finite time horizon is discussed.